2019
DOI: 10.5194/bg-16-2651-2019
|View full text |Cite
|
Sign up to set email alerts
|

Wildfire overrides hydrological controls on boreal peatland methane emissions

Abstract: Abstract. Boreal peatlands represent a globally important store of carbon, and disturbances such as wildfire can have a negative feedback to the climate. Understanding how carbon exchange and greenhouse gas (GHG) dynamics are impacted after a wildfire is important, especially as boreal peatlands may be vulnerable to changes in wildfire regime under a rapidly changing climate. However, given this vulnerability, there is very little in the literature on the impact such fires have on methane (CH4) emissions. This… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…CH4 emissions were also significantly higher in the burnt region than in the non-burnt region and stayed at similar higher levels even into the wet-season, five months after the fire event (Fig 3b). It was previously observed that fire would make the peat dry and effect lower CH4 emissions from the burnt areas because of the lack of moisture (Davidson et al, 2019), but this study has shown that at similar moisture levels, burnt peat has a potential for higher CH4 emissions than the non-burnt peat. This higher CH4 emissions in the fire-affected region may be due to the availability of more labile C due to the denaturation of peat by fire and resultant heat (Sazawa et al, 2018).…”
Section: Discussionmentioning
confidence: 58%
“…CH4 emissions were also significantly higher in the burnt region than in the non-burnt region and stayed at similar higher levels even into the wet-season, five months after the fire event (Fig 3b). It was previously observed that fire would make the peat dry and effect lower CH4 emissions from the burnt areas because of the lack of moisture (Davidson et al, 2019), but this study has shown that at similar moisture levels, burnt peat has a potential for higher CH4 emissions than the non-burnt peat. This higher CH4 emissions in the fire-affected region may be due to the availability of more labile C due to the denaturation of peat by fire and resultant heat (Sazawa et al, 2018).…”
Section: Discussionmentioning
confidence: 58%
“…For example, (i) net C fluxes at the three Heinemeyer et al sites [2] (see the Peatland-ES-UK website [12] ) indicate a potentially high net C uptake on regrowing burnt plots (possibly higher than that of unburnt plots with aging/degenerating heather and soon to offset combustion losses, but this requires a complete burn rotation to allow comparing cumulative C flux budgets versus C stocks estimates); (ii) recent work [14] adds to the prescribed heather burning work [2,3] in highlighting the positive role that charcoal (produced during cool burns or low-severity fires) can have on peatland C storage (e.g. it has the potential to increase peat C stocks by adding recalcitrant Corg in the form of charcoal and further reducing C losses via decomposition of soil organic matter); finally, (iii) a recent study suggests that low-severity fires may reduce methane emissions relative to no burning or high-severity fires in cooler climates [15] . Our greatest concern is that Young et al's unjustified criticisms of specific studies [2,3] have been reproduced within publications of important peatland conservation bodies, such as in the IUCN UK Peatland Programme [16] , which explicitly refer to the two heather burning studies [2,3] as having "presented misleading conclusions" (n.b.…”
Section: Discussionmentioning
confidence: 99%
“…Wildfires may have positive and negative effects on R s , as fire-induced heat suppresses microbes, whilst post-fire ash supplies a greater volume of substrate for microbes and reduces rhizospheric respiration by inhibiting photosynthesis and the development of roots and mycorrhizae Irvine et al, 2007;Kuzyakov and Gavrichkova, 2010 . Based on the large spatial heterogeneity of vegetation cover, fire regime, and increasing deforestation/degradation fires, there is a need for a greater number of studies on the impact of fire on R s and its components across diverse ecosystems, to obtain a better understanding on future C cycles Smith et al, 2018;Hu et al, 2020 . At present, there are very few studies on the fire impacts on CH 4 uptake in the Asian region to reliably assess post-fire impacts on CH 4 flux compared to northern peatlands Davidson et al, 2019;Kumar et al, 2020. Kim 2013 reported that in a white birch forest located at the Teshio Experimental Forest, northern Japan, a low-intensity experimental surface fire did not affect CH 4 uptake, finding no significant alterations in soil properties such as soil moisture, pH, and inorganic N concentrations.…”
Section: Other Natural Disturbancesmentioning
confidence: 99%